Postgraduate Academic Difficulties: Multidimensional Perception Gaps between Students and Coordinators at an Ecuadorian Public University - Manuel Alejandro Basurto Arteaga (Journal of Intelligent Decision Making and Information Science, 2026)
This study examines the academic difficulties perceived by postgraduate students and the perception gaps between students and program coordinators at an Ecuadorian public university. Most available studies rely on a single informant, typically the students themselves, which limits the possibility of contrasting self-perceptions with the institution's own reading of the problem. To address this gap, a cross-sectional, non-experimental, descriptive-comparative design was employed, drawing on 809 cleaned student records from 56 programs and responses from 57 coordinators. Variables were organized into three dimensions: knowledge, time management, and the teaching-learning process. Internal consistency, dimensional structure via confirmatory factor analysis, gaps on a 0-100 scale, Cohen's d effect sizes, and bootstrap confidence intervals were calculated. All three dimensions showed adequate to high internal consistency. Students reported greater difficulty with teacher demands, multiple assignments, and lack of time, whereas coordinators consistently perceived greater intensity, particularly in reading, research, technology, and argumentation; the widest gap was observed for the knowledge dimension (d = 0.59). A robustness analysis by disciplinary area showed homogeneous difficulty levels across the seven areas but heterogeneous student-coordinator gaps, larger in Law and Social Sciences than in Business Administration. The study concludes that institutional support strategies should triangulate student self-perception with the institutional reading of the problem, prioritizing the areas with the largest gaps.